Lens morphogenesis is dependent on Pax6-mediated inhibition of the canonical Wnt/beta-catenin signaling in the lens surface ectoderm - Machon, Ondrej; Kreslova, Jana; Ruzickova, Jana; Vacik, Tomas; Klimova, Lucie; Fujimura, Naoko; Lachova, Jitka; Kozmik, Zbynek (Genesis (New York, N.Y., 2010)
Lens formation in mouse is critically dependent on proper development of the retinal neuroectoderm that is located close beneath the head surface ectoderm. Signaling from the prospective retina triggers lens-specific gene expression in the surface-ectoderm. Supression of canonical Wnt/beta-catenin signaling in the surface ectoderm is one of the prerequisites for lens development because, as we show here, ectopic Wnt activation in the retina and lens abrogates lens formation. Wnt inhibiton is mediated by signals coming from the retina but its exact mechanism is unknown. We show that Pax6 directly controls expression of several Wnt inhibitors such as Sfrp1, Sfrp2, and Dkk1 in the presumptive lens. In accordance, absence of Pax6 function leads to aberrant canonical Wnt activity in the presumptive lens that subsequently impairs lens development. Thus Pax6 is required for down-regulation of canonical Wnt signaling in the presumptive lens ectoderm.
Keywords: oční čočka; Animals; myši transgenní; beta-katenin; Morphogenesis; ektoderm; Repressor Proteins; Embryo, Mammalian; represorové proteiny; Mice, Transgenic; Retina; proteiny Wnt; Lens, Crystalline; morfogeneze; Mice; homeodoménové proteiny; signální transdukce; transkripční faktory paired box; myši; Eye Proteins; Signal Transduction; oční proteiny; Wnt Proteins; Homeodomain Proteins; Paired Box Transcription Factors; Ectoderm; transkripční faktor PAX6; PAX6 Transcription Factor; retina; zvířata; beta Catenin; embryo savčí